STUDI PENENTUAN JADWAL TANAM DAN JADWAL TEBANG TEBU DALAM MEMENUHI KEBUTUHAN BAHAN BAKU PABRIK GULA (Studi Kasus Pada PTPN VII Perkebunan Cinta Manis) - Yunarti, Desi; Sobri, Khaidir; Iswarini, Harniatun (Muhammadiyah University of Palembang, 2016)
Determination Study of Cultivation Schedule of Planting and Harvesting Sugar Cane Schedule in Meeting The Needs of Raw Materials Plant Sugar (Case Study On Sugar cane plantation PTPN VII Cinta Manis). This study aims to determine the method of determining the schedule of planting and harvesting sugar cane schedule in meeting the needs of raw materials plant in PTPN VII Cinta Manis District. And to determine the relationship between the level of availability of raw materials and availability of raw materials factory plant in PTPN VII Cinta Manis District. This research has been conducted in PTPN VII Cinta Manis District. Time data collection was conducted in April - June, 2016. The method used is the case study method, sampling method used is purposive sampling, data collection method used is observation, interview and documentation. Methods of processing and analyzing data is descriptive and to determine the level of availability of raw materials and availability of raw materials using simple linear correlation. The results showed that the determination of the schedule planting and harvest sugar cane in the District PTPN VII Cinta Manis sugar cane maturity based analysis (Cook Early, Middle Cook and Slow Cook). As for the availability of the raw materials and the avaibility of raw materials contained a negative not correlated between the availability of the raw materials and the availability of the raw materials the mill. It happened because availability of the raw materials factory increased sometimes in the follow a decrease in the availability of the raw materials the mill. The direction of the relationship between the availability of the raw materials and the availability of the raw materials factory irregular. Sometime one direction sometime the opposite.